Pawsitive impact: how pet contact ameliorates adult inflammatory stress responses in individuals raised in an urban environment - Langgartner, Dominik; Weimer, Katja; Brunner-Weisser, Jonas; Winkler, Raphael; Mannes, Marco; Huber-Lang, Markus; Sterrett, John D.; Lowry, Christopher A.; Rohleder, Nicolas; Bajrami, Besnik; Luippold, Andreas H.; Groß, Alexander; et al. (Brain, behavior and immunity, 2025)
Background - Individuals raised in an urban environment (URBANs) show an exaggerated inflammatory response to the Trier Social Stress Test (TSST) compared with individuals raised in a rural environment (RURALs). The underlying mechanisms are unclear but may relate to childhood animal contact. As an exaggerated immune (re)activity plays a causal role in the pathogenesis of stress-associated disorders, these findings might explain the higher prevalence of stress-associated disorders in urban vs. rural areas. - Methods - We recruited physically and emotionally healthy male URBANs, raised in a city with more than 40,000 residents either in the absence (noPETs) or presence (PETs) of household pets. Participants were individually exposed to the TSST, and before and after the TSST, blood and saliva were collected for assessment of different stress-related parameters. An additional saliva sample before the TSST was collected for salivary microbiome analysis. Heart rate (HR) and HR variability (HRV) were recorded continuously. Mental and physical health status, early-life and perceived life stress, current animal contact, and subjective strain induced by TSST exposure were assessed using validated questionnaires. - Results - Here we show that adult healthy male noPETs vs. PETs still reported less animal contact during adulthood and were characterized by deficits in their immunoregulatory and intestinal barrier function, which under basal conditions did not translate into a chronic low-grade inflammatory state. This was different under acute psychosocial stress conditions. Exposure to the TSST resulted in a facilitated mobilization of particularly neutrophil granulocytes in noPETs vs. PETs, accompanied by an enhanced pro- and compromised anti-inflammatory systemic stress response. - Conclusion - Together, the presence of pets seems to reduce the risk for URBANs to develop stress-associated disorders later in life (i.e., primary prevention) by facilitating immunoregulatory and barrier functions, in turn preventing an overshooting immune activation in response to acute stressors and chronic low-grade inflammation in response to repeated/chronic stressors.